Asian American literature - Ling, Jinqi (London, UK Bloomsbury Academic, 2023)
"An introduction to Asian American literary studies, this book engages with the conditions, contingencies, and immediate and long-term effects of its major debates. In doing so, it addresses two needs: first, to provide recognizable contours and trajectories for the evolution of Asian American criticism as an ethnic-specific minoritarian formation in the United States; second, to historicize its practices - including polemics, controversies, and ideological ruptures - as an ongoing negotiation undertaken by Asian American critics for a more self-conscious and more adequate representation of the field's interests.

The author examines how the field of Asian American studies has been energized by its demographic transformation, its growing intellectual heterogeneity, its defining moments, and its cross-cutting relationship with the trends of other disciplines. Paying attention to key critical debates and less recognized intellectual contributions, this book explores Asian American literary criticism as a truly open, dynamic, and multi-accentual dialogue"--Back book cover
Introduction: Unfinalizing the Aiiieeeee! moment: a historicist view of the field -- Race, gender, and class: overlapping formations -- The necessity and fiction of "Asian America" -- Intercultural and generational concerns -- The transnational turn -- The social function of literature -- Aesthetic form -- Protocols and the politics of institutionalization -- Emerging interests -- Conclusion: Anti-essentialist critique and the Asian American literary profession.
Includes bibliographical references and index.
Keywords: American literature -- Asian American authors -- History and criticism -- Theory, etc; Asian Americans -- Intellectual life; Criticism -- United States